Odyssey of environmental and microbial interventions in maize crop improvement - Singh, Alok Kumar; Srivastava, Alok Kumar; Johri, Parul; Dwivedi, Manish; Kaushal, Radhey Shyam; Trivedi, Mala; Upadhyay, Tarun Kumar; Alabdallah, Nadiyah M.; Ahmad, Irfan; Saeed, Mohd; Lakhanpal, Sorabh (Frontiers in Plant Science, 2025)
Maize (Zea mays) is India's third-largest grain crop, serving as a primary food source for at least 30% of the population and sustaining 900 million impoverished people globally. The growing human population has led to an increasing demand for maize grains. However, maize cultivation faces significant challenges due to a variety of environmental factors, including both biotic and abiotic stresses. Abiotic stresses such as salinity, extreme temperatures, and drought, along with biotic factors like bacterial, fungal, and viral infections, have drastically reduced maize production and grain quality worldwide. The interaction between these stresses is complex; for instance, abiotic stress can heighten a plant's susceptibility to pathogens, while an overabundance of pests can exacerbate the plant's response to environmental stress. Given the complexity of these interactions, comprehensive studies are crucial for understanding how the simultaneous presence of biotic and abiotic stresses affects crop productivity. Despite the importance of this issue, there is a lack of comprehensive data on how these stress combinations impact maize in key agricultural regions. This review focuses on developing abiotic stress-tolerant maize varieties, which will be essential for maintaining crop yields in the future. One promising approach involves the use of Plant Growth-Promoting Rhizobacteria (PGPR), soil bacteria that colonize the rhizosphere and interact with plant tissues. Scientists are increasingly exploring microbial strategies to enhance maize's resistance to both biotic and abiotic stresses. Throughout the cultivation process, insect pests and microorganisms pose significant threats to maize, diminishing both the quantity and quality of the grain. Among the various factors causing maize degradation, insects are the most prevalent, followed by fungal infections. The review also delves into the latest advancements in applying beneficial rhizobacteria across different agroecosystems, highlighting current trends and offering insights into future developments under both normal and stress conditions.